Predation patterns on the tundra—genetic barcoding of scats from two sympatric fox species - Caitlin Wilkinson; Jan Vigués; Anders Angerbjörn; Karin Norén (Arctic Science, 2023)
In the Arctic tundra, climate-induced emergence of the red fox (Vulpes vulpes (Linnaeus, 1758)), a competitor to the Arctic fox (Vulpes lagopus (Linnaeus, 1758)), is predicted to influence predation patterns of both fox mesopredators. In this study, we (i) identified predator species from scats through an established barcoding approach and (ii) explored the use of a cheap, quick barcoding method of fox feces (n = 103). We investigated differences in diet between the red fox (predicted generalist predator) and Arctic fox (predicted specialist predator) over 2 years with varying prey abundance. We amplified short DNA fragments (<200 bp) from small rodents, birds and hares. For both predators, there was a high frequency of occurrence of rodents (38%–69%) identifying them as primary prey species and birds as secondary prey species (13%–31%). This demonstrates the strength of a straightforward DNA barcoding method for dietary analyses in sympatric fox predators, with species-level resolution of prey. Barcoding is a promising tool for future dietary studies; however, a few methodological improvements, along with extended sampling, are needed for a more complete assessment of fox predation patterns. Integrating high-resolution dietary analyses have great potential to enhance our understanding of predation patterns in Arctic tundra communities.